Smart money kit: an innovative learning tool for kids - Sabri, Mohamad Fazli; Moga Dass, Thinagaran; Ramli, Nurhayatul Nira (International Journal Corner, 2018)
Smart Money Kit: Bright Kids Smart Money is an initiative to raise awareness among public, especially parents and educators on prudent money management among young children. This awareness is resulting of Central Bank of Malaysia's strategy to raise financial literacy in the country among Malaysians. It is a financial education tool targeting mainly young children ages from 6 to 12 years with the objective of educating them on the importance of money and money management in their lives. This financial education kit comes with 10 interactive activities arranged according to children’s ages from the age of 6 to 12 years old. It comprises six basic units covering financial management education i.e. getting to know money, financial goals, needs vs. wants, saving, expenditure and budgeting. This kit has been in the market for the past three years and the researchers conducted an online survey among the parents, teaches, caretakers of the users to measure the impact of Smart Money Kit on their children. A total of 40 respondents have been participated in this online survey and the descriptive analysis has been performed to decode the data. The results shows that, majority of the parents, teachers and caretakers agree that Smart Money Kit has moulded their children becoming financially prudent and 90% of them seen huge difference in their children after being exposed to Smart Money Kit. Hence this kit has been proved to be an effective tool to educate children on financial management and skills, and financial literacy besides able to develop a better financial behaviour and attitude among the children.